Hypothesis on black holes as dimensional portals and information preservation - Khatiwoda, Primos (International Journal of Advanced Astronomy, 2024)
Background: Black holes are traditionally viewed as cosmic entities from which nothing can escape, leading to the notion that information is lost when it crosses their event horizons. This idea is challenged by the information paradox, which raises questions about the preservation of information in light of quantum mechanics.Objective: This manuscript aims to propose a new hypothesis that redefines the nature of black holes by suggesting they function as dimensional portals, preserving information instead of destroying it.Methods: A mathematical model is introduced, featuring a teleportation function, T(D), that describes how information transforms when moving from our three-dimensional space into a higher-dimensional framework.Results: The proposed hypothesis aligns with the principles of quantum mechanics, suggesting that information is retained in a different dimension and may enhance our understanding of black hole thermodynamics, including concepts like Hawking radiation and entropy.Conclusion: The idea of black holes as dimensional portals offers a fresh perspective on the information paradox and presents new avenues for future research in both theoretical and observational physics.